Implementation of Bio-Integrated Farming System: Integration of Aquaponic System with Biofloc Technology as an Attempt to Increase Production in Fish Farmers in Cipadang Village, Pesawaran - Septi Malidda Eka Putri; Nidya Kartini; Putu Cinthia Delis; Rizha Bery Putriani (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The Yang Faulinas II fish farming group from Cipadang Village, Gedong Tataan District, Pesawaran, specializes in catfish farming. However, they frequently face challenges related to water quality, waste management, and rising feed costs. A community service initiative was conducted to address these issues by sharing knowledge and implementing the Bio-Integrated Farming System, which combines aquaponic and biofloc technologies. This system aims to improve water quality and feed efficiency, offering farmers a solution to enhance production while also generating additional income from vegetable cultivation. The integration of aquaponics with the biofloc system allows fish farming and vegetable growing to work together, with plants placed above the biofloc tanks. The methods used in this initiative included lectures, discussions, and hands-on practice. As a result, the participants' knowledge increased by 40%, demonstrating that the adoption of appropriate technology provides a valuable solution and opportunity for fish farmers and communities to grow their businesses and boost production.